Application and effect of SCL film and SK polyurea in aqueduct roughness reduction transformation project. (December 2022) - Li, Chaochao; Li, Mingyang; Xu, Haoli; Gu, Jingchao; Lim, Kar Sing
Abstract: In order to explore the recommended roughness value and application prospect of SCL impermeable film and SK spray polyurea in reducing roughness and increasing flow in water conservancy projects, the prototype observation test is carried out in the typical aqueduct of the pumping irrigation area in Ningxia, and one-dimensional constant flow model based on HEC-RAS is built. The roughness value before and after the engineering transformation of the aqueduct is compared to test the effect of different roughness reducing materials. The results show that:the roughness value of the original concrete aqueduct is about 0.0131, the roughness value of SCL is 0.0115, and the roughness value of SK is 0.0098. The effective reduction of roughness of SCL impermeable film is 12.21%, However, the SK spray polyurea effectively reduced the roughness rate of 25.19%. The effective flow increase of SCL impermeable film is 13.91%, while the effective flow increase of SK scrap polyurea is 33.67%. According to the effect of roughness reducing, flow increasing, and construction technology of the tow different materials, SK spray polyurea will be more suitable for application of water supply and distribution channel renovation project with less cost, easier construction, and more effective. Highlights: The roughness value of the original concrete, SCL and SK is recommend. The effect of SCL and SK on roughness reduction and flow increase is obvious. SK spray polyurea will be more suitable for application with less cost, easier construction, and more effective.